2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2017
DOI: 10.1109/cvpr.2017.307
|View full text |Cite
|
Sign up to set email alerts
|

Learning Diverse Image Colorization

Abstract: Colorization is an ambiguous problem, with multiple viable colorizations for a single grey-level image. However, previous methods only produce the single most probable colorization. Our goal is to model the diversity intrinsic to the problem of colorization and produce multiple colorizations that display long-scale spatial co-ordination. We learn a low dimensional embedding of color fields using a variational autoencoder (VAE). We construct loss terms for the VAE decoder that avoid blurry outputs and take into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 20 publications
0
142
0
2
Order By: Relevance
“…The loss at each pixel is re-weighted based on a weighting factor determined by the rarity of the target colour. This approach prevents the loss function from being dominated by highly common colours and is similar to the approach described in [3].…”
Section: Class Rebalancingmentioning
confidence: 99%
See 4 more Smart Citations
“…The loss at each pixel is re-weighted based on a weighting factor determined by the rarity of the target colour. This approach prevents the loss function from being dominated by highly common colours and is similar to the approach described in [3].…”
Section: Class Rebalancingmentioning
confidence: 99%
“…Recent work on fully automatic image colourisation has shown that Convolutional Neural Networks (CNN) are capable of producing visually appealing colourisation results [15,28,3,8,10]. CNN-based fully automatic approaches can be categorised into two groups: (1) per-pixel descriptor approaches [2,15] and (2) encoder-decoder type architectures [8,28,3,10].…”
Section: Image Colourisationmentioning
confidence: 99%
See 3 more Smart Citations